Photocatalytic Reduction of Co2 Using Zns Pillaring on Kaolin Catalyst - Nik Fatihaf, Nek Kamarzaman (2012)
Increasing of carbon dioxide (CO2) concentration in atmosphere has gain major attention by the researchers. This is due to CO2 ability to absorb heat from the UV light and emits the heat to atmosphere resulted in earth warming. In order to overcome this problem, the researchers come out with many solutions. Conventional method and also Advanced Oxidation Process (AOP) have been invented as a way to reduce the concentration of the predominant greenhouse gases especially CO2. However, AOP has come out as the emerging technologies due to its practicality in reduction process in industry. This study will be focusing on one of the AOP which is photocatalytic reduction process of CO2. In this process, a photocatalyst was needed. In this research, photocatalyst used was ZnS-Kaolin, a combination of semiconductor ZnS and phyllosilicate mineral, Kaolin. ZnS-Kaolin was prepared by using two methods which are hydrothermal method and simpler impregnation method. In this photocatalytic reduction process, the catalyst was dispersed in medium solution, NaOH aqueous and hence help to catalyze the process. The characteristics of the developed ZnS-Kaolin were observed by using Scanning Electron Microscope (SEM) and Thermal Gravimetric Analyzer (TGA). The effect of parameters such as irradiation time and dosage of ZnS-Kaolin used were observed and studied. This process was produced usable products such as methanol and was analyzed by using High Performance Liquid Chromatography (HPLC). Based on the results, from SEM analysis, it was found that raw Kaolin was constructed from hexagonal flakes structure. Meanwhile, both ZnS-Kaolin prepared from Hydrothermal and Impregnation methods are consists of leaf-like layers structure with ZnS nanoparticles deposited on Kaolin structure. From TGA analysis, it was found that ZnS-Kaolin prepared from Hydrothermal method has higher thermal resistance compared to ZnS-Kaolin prepared from Impregnation method. Meanwhile, for photoreduction process of CO2, methanol production was observed to be maximum by using ZnS-Kaolin prepared from Hydrothermal method at dosage of 0.75 g and at 2 hours irradiation time. In conclusion, ZnS-Kaolin prepared by using Hydrothermal method shows better performance in photoreduction process of CO2 compared to ZnS-Kaolin prepared from Impregnation method.